Corporeality : A methodological study of supporting creativity in futures workshops - Tuittila, Satu (fi=Turun yliopisto|en=University of Turku|, 2017)
In futures studies creativity is an essential element needed in imagining and examining the different possible futures to be. Futures imaging, creating options and possibilities of futures, can play a significant role as a cultural force for defining goals. Futures workshops is a regularly used participatory futures method where collective futures imagination is utilised. There are diverse ways to support creativity in futures workshops but a use of corporeal, bodily experiences or multisensory elements for supporting creativity in them is unusual. Corporeality is linked to creativity via concepts of silent and kinaesthetic knowledge where experience and action have important role in knowledge formation. This study is examining the potential of corporeal and multisensory practices in promoting creative futures thinking in the futures workshops method and the interconnectedness of the workshop’s theme and creative practices. This is a qualitative research. A process of two futures workshops from planning to the results with two questionnaires to the participants forms the main source for this study. This is supported by six interviews. The workshops called Papua pataan ja peltoon were providing material for a research network called Kasvunpaikat which created a framework of legumes and sustainability to the workshops. This research was approached from phenomenological perspective emphasising perception, experiential knowledge and corporeality. Creativity in groups and futures research concepts of alternative futures, preferable futures and images of futures create the theoretical frame together with the phenomenology. Corporeal and multisensory activities in the futures workshops are proven useful and potential. They assist in building creative atmosphere for the group works, produce a new kind of silent, embodied knowledge and particularly inspire the participants for futures making. The participants reported several actions after the workshops within the framework of legumes and sustainability. These results evidently indicate the importance of positive multi-layered experiences in supporting commitment to make better futures. The experiences of sharing, learning and the interaction of intellectual, emotional and corporeal are all valuable in creating better futures. Developing further the use of phenomenological perspectives in futures research the experiential, silent, embodied knowledge can be better considered in the context of futures.